Dampak Lingkungan Kerja dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai Instansi Pemerintah: Peran Mediasi Kepuasan Kerja - Denuri Isnanda; Karmila, Karmila; Muhammad Nur Fauzan Akbar; D Hardjowikarto (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine how the work environment and transformational leadership style in government agencies influence performance through job satisfaction. This research used quantitative methods; out of 114 civil servants, 89 people filled out the survey based on Slovin's calculations against Umar. The survey was then conducted via Google Forms using proportional stratified random sampling to select the sample. The data were analyzed using the structural equation modeling (SEM) approach with the partial least squares (PLS) method. According to research, the work environment and transformational leadership improve employee performance, with or without the mediating influence of job satisfaction. It can be seen from the test results that the work environment influences the level of job satisfaction (p < 0.05, t > 3.005), transformational leadership influences job satisfaction (p < 0.001, t > 3.224), the work environment influences employee performance (p < 0.017, t > 2.386), and transformational leadership influences employee performance (p < 0.000, t > 18.026). A supportive work environment, transformational leadership, and employee performance are positively related to job satisfaction, mediating these three aspects, as seen from job satisfaction mediating the relationship between the work environment and employee performance (p < 0.000, t > 4.603). Also, job satisfaction mediates the relationship between transformational leadership and employee performance (p < 0.003, t > 2.922). This shows that job satisfaction mediates the relationship between the company's work environment, transformational leadership, and employee performance. We expect future research to expand our examination to include other public and private sector factors influencing employee performance and job satisfaction.